2013
DOI: 10.4209/aaqr.2012.07.0165
|View full text |Cite
|
Sign up to set email alerts
|

Emission Scenarios and the Health Risks Posed by Priority Mobile Air Toxics in an Urban to Regional Area: An Application in Nashville, Tennessee

Abstract: Toxic air pollutants, also known as hazardous air pollutants, are those that are known or suspected to cause cancer or other serious health effects, such as birth defects or adverse environmental outcomes. The aim of this research was to predict air toxics related health risks due to different emission scenarios by linking Models-3/CMAQ and cancer risk assessments. To demonstrate the effectiveness of this approach, this study was performed on the priority mobile source air toxics (PMSAT) of benzene, 1,3-butadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Currently there exist diverse models that permit the estimation of emission from different pollution sources, especially from mobile sources (Díaz-Robles et al, 2008bDíaz-Robles, 2013). As mentioned above, in the city of Temuco, the program MODEM II has been used to obtain results from these mobile sources (CONAMA, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently there exist diverse models that permit the estimation of emission from different pollution sources, especially from mobile sources (Díaz-Robles et al, 2008bDíaz-Robles, 2013). As mentioned above, in the city of Temuco, the program MODEM II has been used to obtain results from these mobile sources (CONAMA, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ketones, such as methyl ethyl ketone and methyl isobutyl ketone, are toxic chemicals that are widely used in industrial solvents 28 ; inhalation of their vapors and skin contact with liquid ketones are the main routes of human exposure to these compounds 6 . Several studies have shown BTEX pollutants to have a significant adverse impact on human health and classified them as hazardous because they cause serious pathologic conditions, such as asthma, inflammatory disorders, central nervous system dysfunction, and DNA damage, which can potentially lead to cancer 29 , 30 . In plants, high O 3 concentrations affect the growth and yield, whereas in human beings it has been known to exert harmful effects on the eyes and respiratory system, resulting in reduced lung capacity, respiratory distress, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, epidemiology studies have documented adverse respiratory and cardiovascular effects [6,7,8] for populations living in close proximity to major roadways. Studies have shown specific adverse health effects of being exposed to Particulate Matter (PM), including heart diseases [9,10], cancer risk [11] and adverse birth outcomes [12]. Children, pregnant women, elderly and people with existing health issues are some of the vulnerable population groups to adverse traffic-related air pollution.…”
Section: Introductionmentioning
confidence: 99%